Building Reliable Organic Search Systems: Log-Based Analysis of Crawl Waste and Indexation Performance - Tsering Wangchuk Tsering Wangchuk (Techne: Journal of Engineering, Technology and Industrial Applications, 2025)
This article proposes a quantitative, engineering-oriented diagnostic framework that integrates server log telemetry and Google Search Console signals to measure three operational components of SEO performance: crawl efficiency, indexation yield, and visibility volatility, with the goal of translating organic growth constraints into measurable bottlenecks and testable interventions. The framework introduces metrics such as crawl waste rate by URL class, crawl-to-index yield, canonical consistency ratio, discovery and refresh latency, position volatility index for query clusters, and CTR efficiency conditioned on position distribution, and it specifies a reliability workflow in which thresholds and targets are defined as service-level objectives for organic visibility rather than as ad hoc improvement goals. A generic, non-site-specific case design is used to demonstrate how the method distinguishes crawl-budget fragmentation driven by parameterized URL spaces from indexation suppression caused by canonical ambiguity and duplication, and from search outcome instability associated with performance regressions or intent cannibalization. Results show that sites can exhibit high crawler activity while simultaneously suffering low effective crawling of canonical assets, that indexation yield can be materially reduced by inconsistent canonical signals even when sitemaps are valid, and that volatility segmentation reveals which query clusters are constrained by unstable eligibility versus weak snippet competitiveness. The study contributes an applied approach suitable for engineering and applied technology contexts by emphasizing reproducible measurement, constraint localization, and reliability-oriented governance of SEO interventions.